Medical and Economic Implications of Cognitive and Psychiatric Disability of Survivorship - Hopkins, Ramona O.; Girard, Timothy D. (Seminars in Respiratory and Critical Care Medicine, 2012)
Current research indicates that the majority of survivors of critical illness develop post–intensive care syndrome (PICS), which includes new or worsening cognitive or psychiatric disorders that persist for months to years after critical illness. These cognitive impairments and psychiatric disorders are profound and long-lasting, adversely affecting survivors' daily functioning, ability to return to work, and quality of life, as well as altering the lives of their family members. The medical effects of cognitive and psychiatric disability after critical illness translate directly into a large economic burden. A large and growing body of intensive care unit (ICU) survivors with cognitive and psychiatric morbidities presents challenges for research and identification of best practices and interventions, both during and after the ICU, including rehabilitation to prevent or remediate long-term neurological outcomes.
Keywords: critical care; cognitive impairments; depression; anxiety; posttraumatic stress disorder; ICU